2001
DOI: 10.1152/ajpregu.2001.281.1.r302
|View full text |Cite
|
Sign up to set email alerts
|

Early-age heat exposure affects skeletal muscle satellite cell proliferation and differentiation in chicks

Abstract: Exposure of young chicks to thermal conditioning (TC; i.e., 37 degrees C for 24 h) resulted in significantly improved body and muscle growth at a later age. We hypothesized that TC causes an increase in satellite cell proliferation, necessary for further muscle hypertrophy. An immediate increase was observed in satellite cell DNA synthesis in culture and in vivo in response to TC of 3-day-old chicks to levels that were significantly higher than those of control chicks. This was accompanied by a marked inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
3
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 51 publications
5
117
3
6
Order By: Relevance
“…Stored Trig are broken down into non-esterified fatty acids, which then can be processed by the liver and other tissues for energy supply through synthesis of adenosine triphosphate. Also, glucocorticoids inhibit the synthesis of Trig from non-esterified fatty acids (Halevy et al 2001). In the present study, the thermal treatment during late embryonic development had a numerical effect on the serum level of Cort at hatch, while the level of Cort was significantly higher in the TCH group as compared to the control.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Stored Trig are broken down into non-esterified fatty acids, which then can be processed by the liver and other tissues for energy supply through synthesis of adenosine triphosphate. Also, glucocorticoids inhibit the synthesis of Trig from non-esterified fatty acids (Halevy et al 2001). In the present study, the thermal treatment during late embryonic development had a numerical effect on the serum level of Cort at hatch, while the level of Cort was significantly higher in the TCH group as compared to the control.…”
Section: Discussionsupporting
confidence: 45%
“…Finally, Cort is the most common glucocorticoid in birds and its role, under heat stress conditions, is well known (Halevy et al 2001). Glucocorticoids released during stress mobilize lipids from adipose tissue, which supports gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hot/cold irritants could produce thermal variations which may affect the tissue differentiation process. For example, a number of studies have reported that heat stresses can influence cell proliferation [21,36]. The present model does not consider such effects.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction of mortality rate has been measured on a large number of broilers at the production level [9]. This difficulty of accurately measuring mortality has led researchers to develop alternative markers of the efficacy of TC such as growth stimulation [13,25,27], variations in circulating T3 level [3,[26][27][28] and body temperature [8,9,16,26,28].…”
Section: Discussionmentioning
confidence: 99%